Small-Animal dark-field radiography for pulmonary emphysema evaluation - Yaroshenko, Andre; Meinel, Felix G.; Hellbach, Katharina; Bech, Martin; Velroyen, Astrid; Mueller, Mark; Bamberg, Fabian; Nikolaou, Konstantin; Reiser, Maximilian F.; Yildirim, Ali Oe; Eickelberg, Oliver; Pfeiffer, Franz (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2014)
Chronic obstructive pulmonary disease (COPD) is one of The leading causes of morbidity and mortality worldwide and emphysema is one of its main components. The disorder is characterized by irreversible destruction of The alveolar walls and enlargement of distal airspaces. Despite The severe changes in The lung Tissue morphology, conventional chest radiographs have only a limited sensitivity for The detection of mild To moderate emphysema. X-ray dark-field is an imaging modality That can significantly increase The visibility of lung Tissue on radiographic images. The dark-field signal is generated by coherent, small-Angle scattering of x-rays on The air-tissue interfaces in The lung. Therefore, morphological changes in The lung can be clearly visualized on dark-field images. This is demonstrated by a preclinical study with a small-Animal emphysema model. To generate a murine model of pulmonary emphysema, a female C57BL/6N mouse was Treated with a single orotracheal application of porcine pancreatic elastase (80 U/kg body weight) dissolved in phosphate-buffered saline (PBS). Control mouse received PBS. The mice were imaged using a small-Animal dark-field scanner. While conventional x-ray Transmission radiography images revealed only subtle indirect signs of The pulmonary disorder, The difference between healthy and emphysematous lungs could be clearly directly visualized on The dark-field images. The dose applied To The animals is compatible with longitudinal studies. The imaging results correlate well with histology. The results of This study reveal The high potential of dark-field radiography for clinical lung imaging. © 2014 SPIE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: COPD; grating interferometer; pulmonary emphysema; x-ray dark-field; x-ray phase-contrast imaging